Class II malocclusion treatment changes with the Jones jig, Distal jet and First Class appliances - Lorena VILANOVA; José Fernando Castanha HENRIQUES; Mayara Paim PATEL; Rachelle Simões REIS; Roberto Henrique da Costa GREC; Aron ALIAGA-DEL CASTILLO; Silvio Augusto BELLINI-PEREIRA; Guilherme JANSON
Abstract Objective Maxillary molar distalization with intraoral distalizer appliances is a non-extraction orthodontic treatment used to correct molar relationship in patients with Class II malocclusion presenting maxillary dentoalveolar protrusion and minor skeletal discrepancies. This study compares the changes caused by three distalizers with different force systems. Methodology 71 patients, divided into three groups, were included. The Jones jig group (JJG, n=30; 16 male, 14 female, 13.17 years mean age) was treated with the Jones jig for 0.8 years. The Distal jet group (DJG, n=25; 8 male, 17 female, 12.57 years mean age) was treated with the Distal jet for 1.06 years. The First Class group (FCG, n=16; 6 male, 10 female, 12.84 years mean age) was treated with the First Class for 0.69 years. Intergroup treatment changes were compared using one-way ANOVA, followed by post-hoc Tukey's tests. Results Intergroup comparisons showed significantly greater maxillary incisor protrusion in DJG than in FCG (2.56±2.24 mm vs. 0.74±1.39mm, p=0.015). The maxillary first premolars showed progressive and significantly smaller mesial angulation in JJG, FCG and DJG, respectively (14.65±6.31º, 8.43±3.99º, 0.97±3.16º; p<0.001). They also showed greater mesialization in JJG than FCG (3.76±1.46 mm vs. 2.27±1.47 mm, p=0.010), and greater extrusion in DJG compared to JJG (0.90±0.77 mm vs 0.11±0.60 mm, p=0.004). The maxillary second premolars showed progressive and significantly smaller mesial angulation and mesialization in JJG, FCG and DJG, respectively (12.77±5.78º, 3.20±3.94º, -2.12±3.71º and 3.87±1.34 mm, 2.25±1.40 mm, 1.24±1.26 mm, respectively; p<0.001). DJG showed smaller distal angulation of maxillary first molars (-2.14±5.09º vs. -7.73±4.28º and -6.05±3.76º, for the JJG and FCG, respectively; p<0.001) and greater maxillary second molars extrusion (1.17±1.41 mm vs -0.02±1.16 mm and 0.16±1.40 mm, for the JJG and FCG, respectively; p=0.003). Overjet change was significantly larger in DJG compared to FCG (1.79±1.67 mm vs 0.68±0.84; p=0.046). Treatment time was smaller in FCG (0.69±0.22 years vs 0.81±0.33 years and 1.06±0.42 years, comparing it with the JJG and DJG, respectively; p=0.005). Conclusion The three appliances corrected the Class II molar relationship by dentoalveolar changes. The Distal jet produced smaller molar distal angulation than the Jones jig and First Class. The First Class appliance showed less anchorage loss, greater percentage of distalization and shorter treatment time than the Jones jig and Distal jet.